Intussusception of the Bowel in Adults - HM DAR M SHAFI M ARIF JAVED, HJ MAJID (Journal of Fatima Jinnah Medical University, 2018)
Aim: We report our experience in managing adult patients with bowel intussusception with a view to create awareness and bring about improvements in the diagnosis and management of this uncommon condition. Patients and Methods: A critical review of the complete medical records of all adult (older than 18 years) patients with intussusception who were operated by us over an 11 year period (2000 - 2010). Results: The total number of adult patients who underwent surgery for intussusception over the study period was 16. The average age of the patients was 28 years (range 18 - 43). Abdominal pain and vomiting were the commonest presenting symptoms. Eight (50%) patients had acute symptoms (less than 3 days), 2 (12.5%) had sub-acute symptoms (between 3 to 15 days) while 6 (37.5%) patients had chronic symptoms (more than 15 days). The mean duration of symptoms was 4.2 days (range, 1 day to 5 months). CT of the abdomen and pelvis was done in 9 (56.25%) patients and led to a pre-operative diagnosis of bowel intussusception in 8 (88.88%) of these patients. Overall, intussusception was diagnosed pre-operatively in 11 (68.75%) patients and in 7 (43.75%) patients the diagnosis was made at the time of laparotomy. The commonest location for the intussusception was in the small bowel i.e. 12 patients (75%), Jejunojejunal being the commonest type (58.3 % of the 12 patients with small bowel intussusception) while ileoileal intussusception was seen only in 2 patients. Colocolonic site was seen in 2 patients. There was only one patient with Sigmoidorectal intussusception and another patient with ileocaecal colic and appendicocaecal intussusception. A definite pathological cause (lead point) could not be found in 1 patient with small bowel intussusception. All the patients with small bowel intussusception in our series had benign lesions while all the colonic intussusceptions had malignant lead points, i.e. primary adenocarcinoma and lymphoma. All the patients in our series underwent surgery with resection of the effected segment of bowel. There were no deep surgical site infections or anastomotic leaks seen in any of our patients and neither was there any peri-operative mortality in this series. Conclusion: Intussusception of the bowel is infrequently seen in our adult population. Awareness regarding this rare entity and a high index of suspicion, especially in adult patients presenting with subacute or chronic symptoms of bowel obstruction, should lead to an early diagnosis and prompt treatment of the condition. Abdominal CT is the most sensitive imaging modality. Surgical intervention and formal resection of the involved bowel segment is always necessary in adult patients.